Как сделать урок интересным? - Вартанян, А. В.
Статья посвящена новым формам организации отдельных этапов урока русского языка в основной армянской школе с использованием информационных технологий. Предлагается описание урока в девятом классе с использованием презентации и видеоролика при объяснении новой темы. The article is dedicated to the new forms of organizing separate episodes of the lesson of Rusian in the basic Armenian school with the use of Information Technologies. A description of a lesson with the use of videoclip and presentation for expalanation of a new topic in the 9th form is suggested for the attention of specialists of methods of teaching languages and teachers.
Keywords: Практика